Skeletal Muscle Mass Measurement Using Cone-Beam Computed Tomography in Patients With Head and Neck Cancer - Huang, Wei; Tan, Peixin; Zhang, Hongdan; Li, Zhen; Lin, Hui; Wu, Youxing; Du, Qinwen; Wu, Qidi; Cheng, Jun; Liang, Yu; Pan, Yi (Frontiers in Oncology, 2022)
Background and purpose: Head and neck cancer (HNC) patients usually present with malnutrition during radiotherapy, leading to loss of skeletal muscle mass (SMM) and poor clinical outcomes. However, there is no standard modality for measuring SMM. This study aimed to investigate the feasibility of cone-beam computed tomography (CBCT) for assessing SMM and its changes in HNC patients undergoing radiotherapy. Materials and methods: This study was divided into two parts. In part 1 (n = 32), the skeletal muscle area (SMA) based on CBCT and computed tomography (CT) was assessed. In part 2 (n = 30), CT and CBCT were performed, and patients’ weight was measured before and at four different time points during radiotherapy. SMAs were independently identified by three senior radiation oncologists. Results: The SMA on CBCT (SMACBCT) demonstrated excellent interobserver reliability; no significant difference between SMACBCT and SMA on CT (SMACT) was observed in all patients. The SMACBCT and SMACT were highly correlated (r = 0.966; 95% confidence interval = 0.955–0.975; p < 0.001). Bland–Altman analysis revealed that SMACBCT was higher than SMACT. The predicted SMA value using CBCT was similar to the actual value. Moreover, significant differences between SMA and weight loss (F =10.99, p = 0.002), groups and times (F = 3.93, p = 0.013) , and mean percent loss over time (F = 7.618, p < 0.001) were noted. Conclusion: CBCT may be an alternative tool for SMA assessment in HNC patients during radiotherapy.